Application of "Piecewise Fitting of a Model" Technique in Construction of Volume Tables - Jain, R. C.; Raj, M. P.; Rawat, J. K. (Indian Forester, 1991)
The technique of "piecewise fitting of model" is demonstrated in construction of volume table for Eucalyptus from data of block and strip plantations from Punjab. This technique has been found to yield more accurate results as shown by the reduction in average error of estimates.